Are well‐intended Buddhist practices an under‐appreciated threat to global aquatic biodiversity?. Issue 1 (11th January 2019) - Everard, Mark; Pinder, Adrian C.; Raghavan, Rajeev; Kataria, Gaurav
Abstract: The inherently pro‐conservation and humane Buddhist practice of 'live release', entailing the release into the wild of creatures destined for slaughter, poses potentially significant conservation consequences if inappropriate, invasive species are procured for release. This article collates evidence, citing one legal case and other examples, about the risks of the live release of potentially invasive aquatic species that may result in serious, possibly irreversible, conservation threats to aquatic biodiversity and natural ecosystems, with ensuing adverse ecological and human consequences. It is essential that practitioners are aware of these risks if their actions are not to work diametrically against the pro‐conservation and humane intents of the practice. Ensuring that live release occurs safely necessitates raising awareness, with guidance informed by science, to ensure that good intentions do not result in perverse, environmentally destructive outcomes. We propose four simple principles to achieve this, for dissemination to the global adherents of these otherwise entirely laudable practices.